Correlation between duration of treatment and cortisol plasma level in methadone maintained patients - Liljana Ignjatova; Aneta Spasovska Trajanovska (AU-CNS, 2016)
Background. The various endocrine abnormalities reported in heroin addicts and patients in methadone maintenance treatment include: increased thyroxin, triiodothyronine and prolactin levels, and abnormalities in sexual hormone, ACTH and cortisol secretion. The pathophysiological mechanism that has been postulated does explain these findings, including the direct action of heroin or methadone along the hypothalamic-pituitary-adrenal axis. Aim. The aim of this study is to determine the correlation between duration of methadone treatment and cortisol plasma levels in patients treated with methadone maintenance therapy. Methods. The study was carried out at the Centre for Prevention and Treatment of Drug Abuse and Addiction, a part of the Skopje Psychiatric Hospital. The hormonal analysis was carried out at the Department of Clinical Biochemistry, Skopje University Hospital. It is an analytical, cross-sectional study that included 50 male patients in methadone maintenance treatment, divided into two groups. The first group consisted of 34 male patients who had been maintained on methadone treatment for over 2 years. The second group consisted of 16 male patients who had been maintained on methadone treatment for 2 years or less. To discover demographic characteristics we used medical records, and to determine cortisol plasma level we relied on the Chemiluminescence Immunoassay method. The results were analysed statistically by using a t-test for independents samples, χ² test, and Pearson coefficient of linear correlation. Results. The results show that patients treated with methadone for 2 years or less have significantly higher plasma cortisol levels than patients treated with methadone for over 2 years. Conclusions. Longer duration of methadone maintenance treatment tends to normalize the cortisol plasma level.
Keywords: Methadone maintenance therapy; duration of treatment; cortisol plasma level